Astrologia accusata pariter & condemnata. Or The diabolical art of judicial astrologie, receiving the definitive sentence of final condemnation: / being delivered in this following discourse, where the said art is briefly and manifestly opened, justly arraigned, diligently examined, and experimentally condemned by him, who was a student in the same. By John Raunce, sometime a practitioner of astrologie, and student in the magick art. [electronic resource] : (1650)
Summary goes here